(untitled) (SAARC Journal of Agriculture, 2022)
Algal biomass is good source of oils and it can be used for producing biodiesel. The present work is a study of biodiesel production from the algal blooms. Microcystis species was isolated from the blooms and cultured in BG-11 medium. The biodiesel was extracted using alkali catalyzed transesterification method. The trans esterified oil was collected and subjected to GC MS analysis. The FAME profiles showed the presence of unsaturated fatty acids which confirms the presence of biodiesel. The extracted biodiesel was also characterized for the physical properties like fatty acid value, saponification value, iodine value, cetane number, kinematic viscosity, pour point and cloud point. SAARC J. Agric., 20(2): 273-281 (2022)